HPMC- and PLGA-Based Nanoparticles for the Mucoadhesive Delivery of Sitagliptin: Optimization and In Vivo Evaluation in Rats - Nair, Anroop B. (Materials (Basel), 2019)
Mucoadhesive nanoparticles represent a potential drug delivery strategy to enhance the therapeutic efficacy in oral therapy. This study assessed the prospective of developing HPMC- and PLGA-based nanoparticles using a nanospray drier as a mucoadhesive extended release drug delivery system for sitagliptin and evaluated their potential in an animal model. Nanoparticles were prepared using a Buchi(®) B-90 nanospray drier. Optimization of particle size was performed using response surface methodology by examining the influence of spray-drying process variables (inlet temperature, feed flow, and polymer concentration) on the particle size. The prepared nanoparticles were characterized for various physicochemical characteristics (yield, drug content, morphology, particle size, thermal, and crystallographic properties) and assessed for drug release, stability, and mucoadhesive efficacy by ex vivo and in vivo studies in rats. A linear model was suggested by the design of the experiments to be the best fit for the generated design and values. The yield was 77 ± 4%, and the drug content was 90.5 ± 3.5%. Prepared nanoparticles showed an average particle size of 448.8 nm, with a narrow particle size distribution, and were wrinkled. Thermal and crystallographic characteristics showed that the drug present in the nanoparticles is in amorphous dispersion. Nanoparticles exhibited a biphasic drug release with an initial rapid release (24.9 ± 2.7% at 30 min) and a prolonged release (98.9 ± 1.8% up to 12 h). The ex vivo mucoadhesive studies confirmed the adherence of nanoparticles in stomach mucosa for a long period. Histopathological assessment showed that the formulation is safe for oral drug delivery. Nanoparticles showed a significantly higher (p < 0.05) amount of sitagliptin retention in the GIT (gastrointestinal tract) as compared to control. The data observed in this study indicate that the prepared mucoadhesive nanoparticles can be an effective alternative delivery system for the oral therapy of sitagliptin.